Prevalence and Vulnerability to Drug Abuse among Students of High School and Colleges in Riyadh, Saudi Arabia: Cross-Sectional Study by Khadeejeh, Alaa, Nahla, Nourah, Alaa, Beshaier, and Hind (2019) - Mohammed, Alqahtani Jawhrah (International Journal of Innovative Research in Medical Science, 2019)
Drug Abuse is an important medical and public health issue worldwide. In today’s society, adolescent populations oftentimes experience a lot of stressful situations and challenges regarding self-identity, sexuality, drugs, schoolwork, and social life. School nurses are in a position to reach a large number of adolescents, recognize their problem, and foster their general well- being and educational success.